Trends in axillary lymph node dissection for early-stage breast cancer in Europe: impact of evidence on practice - Garcia-Etienne, Carlos A.; Heil, Jörg; Schneeweiss, Andreas (The breast, 2019)
Background: Data from recently published trials have provided practice-changing recommendations for the surgical approach to the axilla in breast cancer. Patients with T1-2 lesions, treated with breast conservation, who have not received neoadjuvant chemotherapy and have 1–2 positive sentinel nodes (Z0011-criteria) may avoid axillary lymph node dissection (ALND). We aim to describe the dissemination of this practice in Europe over an extended period of time. Methods Our source of data was the eusomaDB, a central data warehouse of prospectively collected information of the European Society of Breast Cancer Specialists (EUSOMA). We identified cases fulfilling Z0011-criteria from 2005 to 2016 from 34 European breast centers and report trends in ALND. Data derived from Germany, Italy, Belgium, Switzerland, Austria, and Netherlands. Results 6671 patients fulfilled Z0011-criteria. Rates of ALND showed a statistically significant decrease from 2010 (89%) to 2011 (73%), reaching 46% in 2016 (p<0.001). After multivariable analysis, factors associated with higher probability of ALND were earlier year of surgery, younger age, increasing tumor size and grade, and being operated in Italy (p<0.001). The minimum and maximal rates of ALND in the most recent two-year period (2015–2016) were 0% and 83% in two centers located in different countries (p<0.001). Conclusion Our study demonstrates, a decrease in rates of ALND that started after year 2010 through the end of the study period. Wide differences were observed among centers and countries indicating the need to spread unified clinical guidelines in Europe to allow for homogeneous evidence-based practice patterns.
Members of the EUSOMA Working Group: Mahmoud Danaei, Elmar Stickeler, Dimitri Sarlos, Annemie Prové, Olivia Pagani, Gilles Berclaz, Mario Taffurelli, Elisabetta Cretella, Didier Verhoeven, Andreas Denk, Birgit Carly, Bettina Ballardini, Yvonne van Riet, Rainer Kimmig, Mattea Reinisch, Catia Angiolini, Volker Möbus, Gunter Emons, Kay Friedrichs, Andreas Schneeweiss, Corrado Tinterri, Daniel Egle, Gracienne Staelens, Marion Kiechle, Nadia Harbeck, Fabio Corsi, Lorenzo Menghini, Augusto Lombardi, Lucio Fortunato, Marina Bortul, Jens Huober, Farzaneh Badbanchi, Christoph Tausch
Gesehen am 12.08.2019
Published: 11 March 2019